Melatonin Levels in Saudi Female with Type 2 Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2022)
Melatonin functioning in diabetes mellitus has been investigated, researchers have recorded a decline in plasma melatonin concentrations in diabetes. The current study aimed to assess melatonin levels and investigate their correlation with glucose levels in type 2 diabetic mellitus patients of female gender. Methods: Case-control research was conducted between January 2017 to January 2019 with 100 diabetic participants and 100 healthy participants from Taibah University following a 24-hour fast, glucose and glycated hemoglobin (HbA1c)melatonin, insulin levels, lipid profile were investigated. GraphPad Prism 7 was used for data processing. Daytime melatonin levels decreased considerably in the diabetic group compared to the non-diabetic group (P =.003) and were lower in the diabetic retinopathy group than in the non-retinopathy groups (P = .02). There was a significantly evident and lowering melatonin levels are negatively correlated with blood sugar levels (r = −0.531, P = .001). Also, there were significant negative correlations between the decreasing melatonin levels with the rise in insulin levels and insulin resistance (IR) (r = 0.421, P =.02, r = 0.634, P =.002, respectively). Diabetes patients had lower melatonin levels, which had a negative correlation with higher IR. Changes in melatonin levels may hasten the development of new issues in diabetes patients, particularly retinopathy.